2005
DOI: 10.1200/jco.2005.09.131
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the R-CHOP Study in the Treatment of Elderly Patients With Diffuse Large B-Cell Lymphoma: A Study by the Groupe d'Etude des Lymphomes de l'Adulte

Abstract: Using the combination of R-CHOP leads to significant improvement of the outcome of elderly patients with diffuse large B-cell lymphoma, with significant survival benefit maintained during a 5-year follow-up. This combination should become the standard for treating these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
769
10
27

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,306 publications
(840 citation statements)
references
References 20 publications
34
769
10
27
Order By: Relevance
“…Results from the GELA study have been recently updated with a 5-year median follow-up and showed a persisting advantage for patients treated with R-CHOP (Table 3) (Coiffier et al, 2002;Feugier et al, 2005). In this study, patients with DLBCL and aged 60-80 years were treated either with eight cycles of CHOP or eight cycles of R-CHOP.…”
Section: Rituximab In Diffuse Large B-cell Lymphomamentioning
confidence: 96%
“…Results from the GELA study have been recently updated with a 5-year median follow-up and showed a persisting advantage for patients treated with R-CHOP (Table 3) (Coiffier et al, 2002;Feugier et al, 2005). In this study, patients with DLBCL and aged 60-80 years were treated either with eight cycles of CHOP or eight cycles of R-CHOP.…”
Section: Rituximab In Diffuse Large B-cell Lymphomamentioning
confidence: 96%
“…The addition of the anti-CD20 chimeric monoclonal antibody, rituximab, to anthracycline-based chemotherapy has clearly improved survival outcomes in patients with DLBCL in different clinical settings (e.g., early and advanced stage, and older and younger patients) [35][36][37]. The response to combination chemotherapy appears lower in EBV-positive DLBCL than in EBV-negative DLBCL patients.…”
Section: Management Of Ebv-positive Dlbcl Of the Elderlymentioning
confidence: 99%
“…Recently, rituximab in combination with CHOP (R-CHOP) was established as a new standard of care in patients with DLBCL [1,2].…”
Section: Introductionmentioning
confidence: 99%